Implication of accelerated agricultural growth for household incomes and poverty in Ethiopia: A general equilibrium analysis - Dorosh, Paul A.; Thurlow, James (University of Pennsylvania Press, 2012)
Ethiopia’s economy has experienced rapid growth in recent years. Although growth in agricultural gross domestic product (GDP) from 1998 to 2007 was less rapid than in other parts of the economy, agriculture also performed well, growing faster than the rural population. However, poverty is still severe in Ethiopia and is concentrated in rural areas. To accelerate growth and poverty reduction, Ethiopia’s national strategy affords an important role to agriculture as a source of both growth and development for the broader economy. This is essential given that agriculture is an income source for most of the population.